Coping Processes of South African First-Year University Students: An Exploratory Study (Journal of Student Affairs in Africa, 2021)
South African higher education institutions (HEIs) face significant challenges with high first-year student drop-out rates due to various stressors students are facing. The current study explores the coping of first-year students studying at a South African university. This qualitative study followed anexploratory, descriptive, interpretive strategy to gain a deeper understanding of students' coping during their first academic year at university. Ten participants were recruited through a trusted gatekeeper using purposive voluntary and later snowball sampling methods. Data were collected using theMmogo method® and semi-structured individual follow-up interviews. Interactive qualitative and thematic analyses generated three themes: (1) the availability of and access to coping resources for first-year students; (2) coping strategies first-year students rely on to manage stressors at university; and (3) the effectiveness of selected coping strategies. Understanding the coping of first-year students could assist HEIs in intervening and supporting first-year students appropriately, to enhance theirfirst-year experience (FYE) and overall student well-being. Though limited to a small qualitative study, the contribution to FYE literature is through exploring nuanced coping resources, strategies, and the effectiveness thereof for students, which challenges the 'one-size-fits-all' approach many universitiesmay use. However, there are strategies and awareness of resources that could, in general, be helpful.
Keywords: coping effectiveness; coping resources; coping strategies; first-year experience; first-year students; South African university